The Implementation of Chemical Project Learning Model Integrated with Ethno-Stem Approach on Water Treatment Topic Using Kelor (Moringa oleifera) Seed Extract As Bio-Coagulant - Sudarmin, S.; Kurniawan, Cepi; N, Puji; ., Musyarofah; ., Ariyatun; I, Nurul (KnE Social Sciences, 2019)
Water is one of the natural wealth that is absolutely needed by living things to survive and maintain health. In facts, water treatment is carried out on the raw water that does not meet the standards of clean water quality, therefore, the non-standardized elements need to be eliminated or reduced so that all water meets the applicable standards. One alternative which is available locally is the use of natural coagulants from plants living around us. This research was conducted by students of the UNNES Postgraduate Chemistry Education Magister Program. The process for water treatment employedthepotentialnaturalcoagulantofmoringaseedextractusinganEthno-STEM approach.Thisresearchwascarriedoutasachemicalprojecttask,namelytheproject of using potential bio-coagulant of Moringa oleifera seeds or Moringa plant. In this study, tests were carried out on the use of bio coagulant of moringa seeds extract with various varieties to purify turbid water. The research results concluded that the magisters of chemistry education have been able to design and implement the integrated Ethno-STEM chemical project learning on water puriﬁcation topic using moringa seed extract (Maringo oleifera). In addition, the ﬁndings indicated that the studentswereabletoreconstructethnical-basedscientiﬁcknowledgeinthecontextof STEM;andwaterpuriﬁcationexperimentswithbio-coagulantofMoringaseedextracts. Keywords: Ethno-STEM approach, water treatment, Moringa Oleifera seed extract